Elevated Neurokinin-1 Receptor Expression in Uterine Products of Conception Is Associated With First Trimester Miscarriages - Alwazzan, Ahmad; Mehboob, Riffat; Hassan, Amber; Perveen, Shahida; Sadaf; Gilani, Syed Amir; Ahmad, Fridoon Jawad; Tanvir, Imrana; Babar, Masroor Elahi; Tariq, Muhammad Akram; Ali, Gibran; Akram, Shehla Javed; et al. (Frontiers in Physiology, 2020)
Background Miscarriage is a common complication of early pregnancy, mostly occurring in the first trimester. However, the etiological factors and prognostic and diagnostic biomarkers are not well known. Neurokinin-1 receptor (NK-1R) is a receptor of tachykinin peptide substance P (SP) and has a role in various pathological conditions, cancers, but its association with miscarriages and significance as a clinicopathological parameter are not studied. Accordingly, the present study aimed to clarify the localization and expression for NK-1R in human retained products of conception (POC). The role of NK-1R is not known in miscarriages. Materials and Methods NK-1R expression was assessed in POC and normal placental tissues by immunohistochemistry. Three- to four-micrometer-thin sections of formalin-fixed paraffin-embedded tissues were used for this purpose. Tissues were processed and then immunohistochemically stained with NK-1R antibody. Brain tissue was used as control for antibody. Protein expression was evaluated using the nuclear labeling index (%). Tissues were counterstained with 3,3′-diaminobenzidine (DAB), and microscopy was performed at 10×, 20×, and 40× magnifications. Results Ten human POC tissues and 10 normal placental tissues were studied by immunohistochemistry to demonstrate the localization of NK-1R. The expression of NK-1R protein was high in all the cases of both groups. NK-1R expression showed no notable differences among different cases of miscarriages as well as normal deliveries at full term regardless of the mother’s age and gestational age at which the event occurred. Statistically, no difference was found in both groups, which is in agreement with our hypothesis and previous findings. Conclusion The expression of NK-1R was similar in all the cases, and it was intense. It shows that dysregulation of NK-1R along with its ligand SP might be involved in miscarriages and also involved in normal delivery. Our results provide fundamental data regarding this anti-NK-1R strategy. Thus, the present study recommends that SP/NK-1R system might, therefore, be considered as an emerging and promising diagnostic and therapeutic strategy against miscarriages. Hence, we report for the first time the expression and localization of NK-1R in POC. We suggest NK-1R antagonist in addition to the immunoglobulins and human chorionic gonadotropin to diagnose and treat spontaneous miscarriages.